2021
DOI: 10.1073/pnas.2011411118
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin 6 is a regulator of carcinogenesis in colorectal cancer

Abstract: Early stages of colorectal cancer (CRC) development are characterized by a complex rewiring of transcriptional networks resulting in changes in the expression of multiple genes. Here, we demonstrate that the deletion of a poorly studied tetraspanin protein Tspan6 in Apcmin/+ mice, a well-established model for premalignant CRC, resulted in increased incidence of adenoma formation and tumor size. We demonstrate that the effect of Tspan6 deletion results in the activation of EGF-dependent signaling pathways throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Andrijes et al found that TSPN6 and its adaptor Syntenin-1 negatively mediated the exosomal secretion of the transmembrane form of TGF-α and inhibited Fig. 5 Categories of mechanisms mediating the dysregulation of exosome biogenesis in cancer carcinogenesis in colorectal cancer [149]. For the ESCRT independent pathway, both caveolin-1, flotillins, and Rab31 are ubiquitously overexpressed in cancer and promote cancer progression and chemoresistance by their function in controlling exosomes secretion [45,50,150].…”
Section: Aberrant Expressionmentioning
confidence: 99%
“…Andrijes et al found that TSPN6 and its adaptor Syntenin-1 negatively mediated the exosomal secretion of the transmembrane form of TGF-α and inhibited Fig. 5 Categories of mechanisms mediating the dysregulation of exosome biogenesis in cancer carcinogenesis in colorectal cancer [149]. For the ESCRT independent pathway, both caveolin-1, flotillins, and Rab31 are ubiquitously overexpressed in cancer and promote cancer progression and chemoresistance by their function in controlling exosomes secretion [45,50,150].…”
Section: Aberrant Expressionmentioning
confidence: 99%
“…Moreover, TSPAN6 can bind to the EGFR suggesting that it directly negatively regulates EGFR phosphorylation and signaling. Indeed a recent study has shown that TSPAN6 controls the production of the extracellular vesicles containing the transmembrane form of TGF-alpha, a EGFR ligand, and thereby downregulates EGFR signaling [ 42 ]. In this newly described mechanism, TSPAN6 is physically linked to TNF-alpha via the adapter protein syntenin-1, and upon TSPAN6 downregulation increased production of extracellular tm-TGF-alpha occurs leading to increased EGFR signaling [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed a recent study has shown that TSPAN6 controls the production of the extracellular vesicles containing the transmembrane form of TGF-alpha, a EGFR ligand, and thereby downregulates EGFR signaling [ 42 ]. In this newly described mechanism, TSPAN6 is physically linked to TNF-alpha via the adapter protein syntenin-1, and upon TSPAN6 downregulation increased production of extracellular tm-TGF-alpha occurs leading to increased EGFR signaling [ 42 ]. Although our findings show that TSPAN6 knockdown phenocopies DLG1 and SCRIB knockdown, and our analysis in Drosophila has linked Tsp29Fb to Scrib/Dlg1 regulation/function [ 14 ], and that Scrib/Dlg1 are known to regulate Ras signaling in Drosophila and mammalian cells [ 11 , 30 , 43 , 44 ], since TSPAN6 does not bind to DLG1 or SCRIB, it is likely that these proteins regulate EGFR-RAS signaling by parallel pathways, with TSPAN6 functioning at the level of the EGFR by binding to it and inhibiting its activation, and SCRIB/DLG1 directly binding to and negatively regulating ERK activation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of TSPAN6 is frequently decreased or even lost in colorectal cancer tissues, and correlates with favorable survival. TSPAN6 deletion facilitates colorectal cancer development and results in the activation of EGF-dependent signaling pathways through increased production of the transmembrane form of TGF-α (tmTGF-α) associated with extracellular vesicles [ 83 ]. Liang G. and colleagues found that TSPAN12 could inhibit tumor growth of non-small lung cancer cells [ 77 ].…”
Section: Introductionmentioning
confidence: 99%